RNA recombination at Chikungunya virus 3'UTR as an evolutionary mechanism that provides adaptability - Filomatori, Claudia Veronica (2019)
The potential of RNA viruses to adapt to new environments relies on their ability to introduce changes in their genomes, which has resulted in the recent expansion of re-emergent viruses. Chikungunya virus is an important human pathogen transmitted by mosquitoes that, after 60 years of exclusive circulation in Asia and Africa, has rapidly spread in Europe and the Americas. Here, we examined the evolution of CHIKV in different hosts and uncovered host-specific requirements of the CHIKV 3'UTR. Sequence repeats are conserved at the CHIKV 3'UTR but vary in copy number among viral lineages. We found that these blocks of repeated sequences favor RNA recombination processes through copy-choice mechanism that acts concertedly with viral selection, determining the emergence of new viral variants. Functional analyses using a panel of mutant viruses indicated that opposite selective pressures in mosquito and mammalian cells impose a fitness cost during transmission that is alleviated by recombination guided by sequence repeats. Indeed, drastic changes in the frequency of viral variants with different numbers of repeats were detected during host switch. We propose that RNA recombination accelerates CHIKV adaptability, allowing the virus to overcome genetic bottlenecks within the mosquito host. These studies highlight the role of 3'UTR plasticity on CHIKV evolution, providing a new paradigm to explain the significance of sequence repetitions.